Role of Nigella sativa oil on histological features and androgenicity of nicotine treated male Sprague dawley reproductive system / Lina binti Samsudin - Samsudin, Lina (2015)
Tobacco is a plant from which nicotine, the alkaloid in cigarette is known to have detrimental effects on male reproductive system, can be sourced. As for Nigella sativa is a plant which has been used in culinary and also as traditional medicine since the antiquity by worldwide society. The remedial value of Nigella sativa has been attributed to its antioxidant properties. This study was conducted to investigate the protective effects of Nigella sativa oil on spermatogenic, leydig and sertoli cell count, histological features and androgenicity of nicotine treated male rat reproductive system. Thirty male Sprague dawley rats, aged 7 – 9 weeks, with 150 – 250g body weight were divided into five groups; saline (S), nicotine (N), corn oil (CO), Nigella sativa (NS) or nicotine-Nigella sativa (NNS). The S and N groups were intramuscularly (i.m.) injected with 0.1ml/100g saline and 0.5mg/100g nicotine, respectively. The CO and NS groups were force-fed with 0.1ml/100g corn oil and 6μl/100g Nigella sativa oil, respectively. The NNS group received both nicotine and Nigella sativa oil with similar dosage and mode of administration to the N and NS groups. The rats were then sacrificed after 100 days of treatment. The testes, seminal vesicles and prostate glands were extracted and fixed in 10% formalin solution prior to histological and immunohistochemical studies. The NS (34.98±2.12) and NNS (30.35±1.93) groups showed a significant higher number of spermatogonia compared to the N group (p<0.05). The number of spermatocytes (57.77±1.76) and spermatid (176.23±5.12) of the NS group were significantly higher compared to the N and NNS groups. In addition, a significant higher number of spermatozoa was observed in the NNS (69.20±3.02) compared to the N (46.22±2.68) and NS (60.22±3.34) groups. The cells counts of the NS group were significantly higher for Sertoli (20.83±0.87) and Leydig (42.77±1.77) cells than the N and NNS groups. The histoarchitecture of the testes, prostate gland and seminal vesicle were noted to be disrupted in the N group. However, it was found to be similar to the S group with co-administration of Nigella sativa oil as seen in the NNS group. The NS and NNS groups also exhibited high intensity of staining for the androgen receptor in all of the tissues examined as opposed to the N group. In brief, this study suggested that nicotine caused damage to the male reproductive system while Nigella sativa oil was shown to have protective properties on the detrimental effects caused by the nicotine.